Effects of Insulin against Aluminium Induced Neurotoxicity in Wistar Rats - Amir Alam; Garima Bansal (Pharmacology and Clinical Pharmacy Research)
Aluminium toxicity is well known to cause neurotoxicity leading to Alzheimer disease with dementia. The aim of the present study is to evaluate the effects of Insulin in Aluminium induced neurotoxicity. Thirty male wistar rats randomized into three groups (group V, C, T) of ten each were used for the study after obtaining institutional animal ethics committee approval. Chronic aluminium neurotoxicity was induced in the rats and the neurobehavior was evaluated using Morris water maze test, elevated plus maze test and rotarod test using standard methodologies. Group C rats exhibited significant deviation in performance of behavioural test of the study during day 1 (Morris water maze test- 18.6±9.5, elevated plus maze test- 34.9±1.9, rotarod test- 118.6±15.2) and day 30 (Morris water maze test- 64.5±4.6, elevated plus maze test- 72.1±3.9, rotarod test- 110.7±9.3). Rats of group T showed decrease in behavioural changes induced by aluminium toxicity (P value: Morris water maze test-0.0002, elevated plus maze test- 0.0007 and rotarod test- 0.015). Insulin may play a role in neuroprotection against toxicity similar to that of aluminium induced neurotoxicity.